Peran Pengembangan Ekonomi Umat Terhadap Penguatan Moderasi Beragama Dan Kepentingan Kinerja di Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Abdul Kholid Azhari; Agung Setia; Marliyah Marliyah (Pusat Riset dan Inovasi Nasional, 2024)
The Ministry of Religion in the program and target of ummat economic development activities adopts the vision of the Ministry of Religion in the Regulation of the Minister of Religion of the Republic of Indonesia Number 18 of 2020 concerning the Ministry of Religion Strategic Plan for the 2020-2024 Period, which is prepared on the basis of the RPJMN 2020-2024 and is guided by the 2005-2025 RPJPN, Efforts to empower the Ummah Economy which aim to mobilize resources to empower the economic potential of the ummah in order to make the ummah prosperous through an increase in the level of productivity, it is hoped that resources which include humans and nature can be further improved in their management and development, so that it is hoped that the economic welfare of the ummah will be achieved which is one of the reinforcements of religious moderation relations to fellow human beings. The purpose of this study was to determine the role of human resources in completing official travel reports effectively and efficiently and what are the obstacles in carrying out official travel procedures. This research uses descriptive qualitative research, and uses primary data sourced from direct observation at the Regional Office of the Ministry of Religion of North Sumatra. The results in this study indicate that in answering the problems of official travel report files it is necessary to improve the work ability of employees or employees is an important element in order to achieve goals in the economic development of the people in the office of the Ministry of Religion of North Sumatra province.